Structural homology between lymphocyte receptors for high endothelium and class III extracellular matrix receptor. - Gallatin, W M (1989)
We have identified extensive structural homology between one type of heterotypic adhesion receptor (HAR) involved in lymphocyte interactions with high endothelium in lymphoid organs and a collagen-binding protein, termed class III extracellular matrix receptor (ECMRIII), expressed on most nucleated cell types. Both receptors have been described as heterogeneous 90-kDa transmembrane glycoproteins, referred to here as gp90. Monoclonal anti-HAR antibodies, Hermes-1 and Hutch-1, and monoclonal anti-ECMRIII antibodies, P1G12 and P3H9, were utilized to compare the two receptors. (i) All these monoclonal antibodies immunoprecipitated major gp90 components as well as uncharacterized additional higher molecular mass antigens of 120-200 kDa in human and macaque fibroblasts and peripheral blood mononuclear cells. (ii) Competitive binding analyses with the antibodies identified distinct epitopes present on gp90. (iii) Enzymatic and chemical digestions generated identical peptide fragments from all the antigens in human and macaque fibroblasts and peripheral blood mononuclear cells. (iv) Sequential immunoprecipitation with P1G12 followed by the other monoclonal antibodies indicated that all gp90 species reactive with Hermes-1 and Hutch-1 also expressed the P1G12 defined epitope. In reciprocal experiments, Hermes-1 and Hutch-1 immunoprecipitation did not completely remove all P1G12-reactive gp90 from cellular extracts. One inference from these data would be that gp90 is serologically heterogeneous, encompassing HARs as a major subset of this broadly expressed class of molecules.